Reading comprehension and mathematics problem solving in students from a private school of Lima - Canales Alfaro, Mónica Yolanda (2019)
The current investigation uses a non-experimental and correlational design, trying to establish if reading comprehension is linked with mathematics problem solving in a sample of 115 students of fifth grade from a private school of Lima, to whom the following instruments were applied: the Questionnaire of Evaluation of the Reading Comprehension ACL5 made by Catalá, Catalá, Molina and Monclús (2007), and the Test of Evaluation of the Mathematics Skills, made by García, García, González, Jiménez, Jiménez Mesa and González (2009). Both tests were submitted to a pilot test that has determined consistent levels of validity and reliability. The statistical results indicate us that the studied variables are related (r = 0,69). Moreover, it is possible to appreciate the existence of significant relations between the dimensions of both variables. Furthermore, it is possible to appreciate that in the case of the variable “reading comprehension”, the descriptive results show that the 50,4% is located in the medium level, while the lower level reaches 27,0% and the higher level, 22,6%. In the case of the variable “mathematics problem solving”, the descriptive results indicate that the 51,3% is located in the medium level, while the lower level reaches 23,5% and the higher level, 25,2%.